Analysis of ChatGPT Utilization by Islamic Education Students from the Perspective of the Foundations of Islamic Education - Hasan Basri; Yuni Purnama Sari (al-Afkar, Journal For Islamic Studies, 2026)
Advances in information and communication technology, particularly in the form of artificial intelligence such as ChatGPT, have brought significant changes to the world of education, including in Islamic Religious Education (PAI). This study aims to analyze the use of ChatGPT by 7th-Semester Islamic Religious Education (PAI) students in Class D, 2024, at UIN Sunan Gunung Djati Bandung, focusing on its suitability with the foundations of Islamic Education. This technology, although offering easy access and efficiency in learning, is not designed to consider profound Islamic values, such as wisdom, etiquette, and tawhid, which are the basic principles of Islamic education. This study used a quantitative approach with a survey method, collecting data through questionnaires distributed to 34 PAI students. The analysis results show that students tend to use ChatGPT in a positive and responsible manner, despite the potential for dependence on this technology, which can reduce the depth of understanding of the study of the Qur'an and Hadith. With a very high reliability of the research instrument (0.946), these findings indicate that the use of ChatGPT can enrich the learning of PAI students, provided that it continues to consider the principles of Islamic education in its application. This research confirms that technology integration in Islamic education, when conducted with moral and ethical awareness, can enrich learning without neglecting essential religious values. Going forward, technology integration, such as ChatGPT, in Islamic education can continue to be developed while maintaining harmony between technological innovation and Islamic scientific principles.